2003
DOI: 10.1109/jsen.2003.820333
|View full text |Cite
|
Sign up to set email alerts
|

A displacement sensor for nonmetallic hydraulic cylinders

Abstract: A sensor was developed to provide signals proportional to the position of the rod in a hydraulic cylinder. The sensor has a coil winding in the shell of the cylinder. The sensor operates by sensing the change in the coil impedance as the rod moves in the cylinder. This paper describes the construction of the cylinder and the sensor, and the performance evaluation of the sensor. Several different materials were placed in the rod and tested. For the cylinder tested, an aluminum core provided the highest precisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…It needs large number of sensors with complicated signal processing and expensive non ferromagnetic iron rod. A simpler method is to measure inductance of solenoid coil around cylinder [4]- [6]. The problem of this solution is slow response and large temperature dependence [5]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…It needs large number of sensors with complicated signal processing and expensive non ferromagnetic iron rod. A simpler method is to measure inductance of solenoid coil around cylinder [4]- [6]. The problem of this solution is slow response and large temperature dependence [5]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve previous method, we returned to the simple concept of variable inductance sensor. This type of sensor was already used for hydraulic cylinders with composite non-conductive shell [3]. We have shown that variable inductance sensors can also be used to measure position of the piston in pneumatic cylinder with aluminum shell.…”
Section: Introductionmentioning
confidence: 99%
“…The root mean square error (RMSE) for linearity in percentage value as an indicator [15] for representation of fitness of measured values to the linear curve fit is calcu lat ed about 0.26% for iron rotating disk at 300 Hz. Fig.…”
Section: A Experimental Setupmentioning
confidence: 99%